PAJAGA BONE BALLA DANCE AS ETHNO PEDAGOGY IN LUWU SOCIETY, SOUTH SULAWESI - Ilham Haruna; Jaeni B Wastap; Sukmawati Saleh (Universitas Negeri Makassar, 2023)
This research intends on the didactic constellation of the Luwu Kingdom community to shape the character of descendants by the convention on pangadereng values. The didactic is implemented into the cultural cohesion of dance. This research uses qualitative analysis with an ethnopedagogical or ethno-didactic approach. The continuum of this research looks at the factors in obtaining evidence, namely observation, in-depth interviews, field and non-field notes (literature review), and documentation. The didactic convergence of the Pajaga Bone Balla dance becomes a distinctive form to create a human entity with superior character, not only for particles but as a whole in every living thing. Dancers who can practice the didactic value of the dance are human beings with a degree of self-control over all lustful dependencies. The Pajaga Bone Balla dance which is intended for the sons and daughters of the Luwu dynasty is a means of life meditation to forge character to become a complete human being. Recursive research is needed to find deeper and more coherent conclusions about the constellation of intangible cultural heritage. Dissemination of revolutionary data is needed to minimize the invalidity of an object of research. The deterministic intangible culture, in this case, the Pajaga Bone Balla dance, both whose didactic dance cohesion for male dancers (Pajaga Bone Balla Tulolo) and female dancers (Pajaga Bone Balla Anak Dara), requires transparency from the aristocrat layer at the level of Luwu sovereignty so that this cultural heritage is maintained.